2008
DOI: 10.1002/cncr.23989
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation of the Wnt/β‐catenin signaling antagonist Dkk‐3 is associated with poor survival in gastric cancer

Abstract: Objective Infliximab treatment results in a decrease in synovial cellularity as early as 48 hours after initiation of therapy in patients with rheumatoid arthritis (RA). This study was undertaken to investigate whether infliximab induces apoptosis within the first 24 hours after infusion. Methods The percentage of apoptotic cells was determined by flow cytometry in blood drawn from 21 patients directly before, 1 hour after, and 24 hours after infliximab infusion. Synovial tissue samples obtained before, 1 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 62 publications
5
89
1
Order By: Relevance
“…Furthermore, methylation could provide useful information regarding prognosis. Yu et al reported that patients with methylation of Dkk-3, a Wnt/b-Catenin signaling antagonist, had a significantly shorter survival than patients with no methylation, in a study of primary gastric cancers (18). There have been many studies on the relationship between the methylation of tumor-suppressor genes and the response to chemotherapy in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, methylation could provide useful information regarding prognosis. Yu et al reported that patients with methylation of Dkk-3, a Wnt/b-Catenin signaling antagonist, had a significantly shorter survival than patients with no methylation, in a study of primary gastric cancers (18). There have been many studies on the relationship between the methylation of tumor-suppressor genes and the response to chemotherapy in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis of the gastrointestinal epithelium is 87 [47,[69][70][71][72][73][74][75]232] Fzd-3 [78] CTNNB1 [9,[88][89][90][91][92][93]96,97] LRP6 [228] TCF7L2 [98][99][100] PPN [79] CDH17 [80] EZH2 [81] HMGA1, HMGA2 [210,211] YY1 [86] TC1 (C8orf4) [201,202] miR-17-92 [161] mir-10a [168] has-miR-335 [166] hsa-miR-375 [163] Downregulation or function inhibition in gastric cancer Downregulation by hypermethylation Inactivation by miRNAs APC [145,146] APC [175] sFRP1, sFRP2, sFRP4, sFRP5 [78,96,149] AXIN2 [159] WIF-1 [144,149] EZF1 [78] Dkk-1, Dkk-2, Dkk-3 [59,144,148,…”
Section: Wnt/b-catenin Pathway In Gastric Carcinogenesismentioning
confidence: 99%
“…Several other tumor suppressor genes that function through modulating Wnt/b-catenin signaling were found silenced in gastric cancer, such as members of the sFRP and Dkk gene families. CpG methylation-depending silencing of sFRP1, sFRP2, sFRP4, sFRP5, HSulf-1, WIF-1, RUNX3 as well as, Dkk-1, Dkk-2 and Dkk-3 has been frequently observed among gastric cancer cells lines and primary specimens [59,96,108,144,147,148] . In addition, Yu et al [148] showed by multivariate analysis that Dkk-3 methylation was associated significantly and independently with poor disease survival in gastric cancer, but not in colorectal cancer.…”
Section: Loss Of Wnt Repressor Function In Gastric Cancermentioning
confidence: 99%
“…15 Wnt/b-catenin signaling and bcatenin target molecule cyclin D1 are important in promoting GC progression and chemoresistance. [16][17][18] We hypothesize that NR4A2 is activated in an inflammatory microenvironment, participates in an evolutionary process from inflammation to cancer via affecting PKA and/ or OPN-b-catenin-cyclin D1 pathways, and promotes the progression of GC. However, the role of NR4A2 in the pathogenesis of GC remains unknown.…”
Section: Introductionmentioning
confidence: 99%